2010
DOI: 10.1016/s0027-9684(15)30574-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrated Risk Counseling for Cancer and Cardiovascular Disease in African Americans

Abstract: Objective We evaluated a risk counseling intervention designed to enhance understanding about risk factors for cancer and cardiovascular disease, to improve self-efficacy for diet and physical activity, and to increase intentions to eat healthier and be physically active. Methods We conducted a quasi-experimental study developed by academic investigators and community stakeholders to evaluate the effects of integrated risk counseling in a community-based sample of African American adults (n = 101). The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…27,28,33,34 Various aspects of the social environment have been addressed in previous health behavior interventions through programming in which participants are asked to complete study activities with a support person or friend, or in which the intervention is delivered in a group setting. 20,35,36 Interventions that specifically target individuals who live in public housing units or work in particular settings are other examples of programs that address aspects of the social environment. 37,38 Targeted interventions and those that address social support and interpersonal relationships have an important role to play in health promotion and disease prevention among African Americans, especially since these approaches also provide opportunities for healthy behaviors to be modeled in a supportive environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28,33,34 Various aspects of the social environment have been addressed in previous health behavior interventions through programming in which participants are asked to complete study activities with a support person or friend, or in which the intervention is delivered in a group setting. 20,35,36 Interventions that specifically target individuals who live in public housing units or work in particular settings are other examples of programs that address aspects of the social environment. 37,38 Targeted interventions and those that address social support and interpersonal relationships have an important role to play in health promotion and disease prevention among African Americans, especially since these approaches also provide opportunities for healthy behaviors to be modeled in a supportive environment.…”
Section: Discussionmentioning
confidence: 99%
“…This research was conducted as part of an academic-community partnership; 20,21 participants were African American men and women who were residents in an urban city. To be eligible for participation, individuals had to be ages 18–75 and be a current resident in the Philadelphia, PA metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this approach, we first conducted a multilevel needs assessment with African American residents in the Philadelphia, PA metropolitan area and found that community members were concerned about chronic health conditions such as cardiovascular disease (CVD) and cancer and wanted greater education about obesity reduction and prevention through lifestyle modification and health behavior change [18]. Next, we used developed an integrated approach for providing education about risk factors for chronic diseases to address the priorities identified by community residents as part of a pilot study [20]. As part of this quasi-experimental study, participants received education about the overlap in risk factors for cancer and CVD and used techniques from motivational interviewing were used to improve selfefficacy for diet and PA.…”
Section: Introductionmentioning
confidence: 99%
“…As part of this quasi-experimental study, participants received education about the overlap in risk factors for cancer and CVD and used techniques from motivational interviewing were used to improve selfefficacy for diet and PA. Integrated risk factor education led to significant increases in confidence to make behavioral changes in our pilot quasi-experimental design [20]. To further inform the development of an intervention that addressed community priorities, we also examined barriers and facilitators to PA and FV intake in a community-based sample of African Americans who were recruited from the Philadelphia, PA metropolitan area.…”
Section: Introductionmentioning
confidence: 99%